THE CRISIS OF EFFECTIVENESS OF INTERNATIONAL ORGANIZATIONS IN THE CONTEMPORARY SECURITY SYSTEM - Бубнов, Ігор (SWorldJournal, 2026)
The article analyzes the phenomenon of the crisis of effectiveness of international organizations in the contemporary international security system under conditions of transformation of the world order and increasing complexity of global threats. The key